Stock de carbono en la biomasa de seis especies forestales representativas de 4 parcelas del arboretum “el huayo”, ciefor, Puerto Almendra, Loreto-Perú, 2024 - Fasabi Ramírez, Maximo Alfonso (2024)
The study was conducted in four plots (VI, VII, VIII, and IX) of the “El Huayo” Arboretum, located in a medium terrace forest within CIEFOR, Puerto Almendra, San Juan Bautista, Perú. All forest species were evaluated to determine those with the highest importance value index (IVI) or greater representativeness. Six species were identified as the most abundant and dominant: Eschweilera decolorans Sandwith (7.41% IVI), Nealchornea yapurensis Huber (3.77% IVI), Pourouma cucura Standl. & Cuatrec. (3.60% IVI), Parkia nitida Miq. (3.36% IVI), Cedrelinga cateniformis (Ducke) Ducke (2.30% IVI), and Triplaris peruviana Fisch. & C. A. Mey. ex C. A. Mey. (1.99% IVI). These species exhibited the highest carbon storage in aboveground biomass, accounting for a subtotal of 144.69 tnC, with a total carbon stock of 406.54 tnC in the study area. The results show a high degree of variability among the collected data, which is highly heterogeneous. In this context, Eschweilera decolorans Sandwith displayed the highest carbon storage in aboveground biomass compared to the other species. Since the data do not follow a normal distribution, the differences in carbon content stored in the biomass of the six most representative forest species are statistically significant. The studied species exhibit varying amounts of carbon storage in aboveground biomass, depending on species-specific diameter measurements and the applied allometric equations.